Fibrogenesis in LAMA2-Related Muscular Dystrophy Is a Central Tenet of Disease Etiology - Anthony Accorsi (Frontiers in Molecular Neuroscience, 2020)
LAMA2-related congenital muscular dystrophy, also known as MDC1A, is caused by loss-of-function mutations in the alpha2 chain of Laminin-211. Loss of this protein interrupts the connection between the muscle cell and its extracellular environment and results in an aggressive, congenital-onset muscular dystrophy characterized by severe hypotonia, lack of independent ambulation, and early mortality driven by respiratory complications and/or failure to thrive. Of the pathomechanisms of MDC1A, the earliest and most prominent is widespread and rampant fibrosis. Here, we will discuss some of the key drivers of fibrosis including TGF-beta and renin–angiotensin system signaling and consequences of these pathways including myofibroblast transdifferentiation and matrix remodeling. We will also highlight some of the differences in fibrogenesis in congenital muscular dystrophy (CMD) with that seen in Duchenne muscular dystrophy (DMD). Finally, we will connect the key signaling pathways in the pathogenesis of MDC1A to the current status of the therapeutic approaches that have been tested in the preclinical models of MDC1A to treat fibrosis.